Bunnicula : the graphic novel - Howe, James, 1946-; Donkin, Andrew (Atheneum Books for Young Readers, 2022)
Though scoffed at by Harold the dog, Chester the cat tries to warn his human family that their foundling baby bunny must be a vampire.